Virtually Being Einstein Results in an Improvement in Cognitive Task Performance and a Decrease in Age Bias - Banakou, Domna; Kishore, Sameer; Slater, Mel (Frontiers in Psychology, 2018)
The brain's body representation is amenable to rapid change, even though we tend to think of our bodies as relatively fixed and stable. For example, it has been shown that a life-sized body perceived in virtual reality as substituting the participant's real body, can be felt as if it were their own, and that the body type can induce perceptual, attitudinal and behavioural changes. Here we show that changes can also occur in cognitive processing and specifically, executive functioning. Fifteen male participants were embodied in a virtual body that signifies super-intelligence (Einstein) and 15 in a (Normal) virtual body of similar age to their own. The Einstein body participants performed better on a cognitive task than the Normal body, considering prior cognitive ability (IQ), with the improvement greatest for those with low self-esteem. Einstein embodiment also reduced implicit bias against older people. Hence virtual body ownership may additionally be used to enhance executive functioning.